Use of Water Resource in Costa Rica: The Case of Municipal Aqueducts - Hernández Cruz, Orlando Josué (2020)
The purpose of this article is to present the results on the use of water resources by municipal aqueducts in Costa Rica. These results are part of an investigation that was carried out as a seminar for the School of Public Administration. Although it is recognized the importance of always bearing in mind the concept of the integral management of water resources, in this opportunity only the results on the use of water according to its factors of coverage and quantity, quality and cost, and water culture are presented.